Isoeritrólise neonatal eqüina - Rossi, Larissa Sartori [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
Equine neonatal isoerythrolysis is a neonatal foals’ illness. Results from the incompatibility of blood type between the foal and the mare and mediated by maternal antibody absorbed by the colostrum against foal’s red blood cells. Characterized by a type ll hypersensitivity reaction, where the exhibition of the organism to a strange antigen, that it takes the sensitization of the lymphocytes B that after the removal of the antigens by the reticule-endothelial system the production of immunoglobulin is decreased, with the formation of cellular immunological will cause the occurrence of the illness in foal of sensitized mares. The most important clinical signs are severe anemia and jaundice, and this illness should be differentiated of other as: hemolysis induced by bacterial toxins, diseases of the hepatobiliary system, disseminated intravascular coagulation and incompatibility in blood transfusions. Like the sensitization happens during the previous incompatible foal’s birth, most cases occur in foals of multiparous mares. However during the first pregnancy the mare can generate a foal with neonatal 7 isoerythrolysis if she have developed placental anomaly in the beginning of the pregnancy which blood cells in her circulation

Isoeritrólise neonatal eqüina é uma enfermidade que acomete potros neonatos. Causada devido a incompatibilidade de grupo sangüíneo entre o potro e a égua e mediada por anticorpos maternos absorvidos através do colostro contra hemácias do potro. Caracterizada por uma reação de hipersensibilidade tipo ll, ou seja, mediante a exposição do organismo a um antígeno estranho ocorre a sensibilização dos linfócitos B e, após a remoção dos antígenos pelo sistema retículoendotelial, a produção de imunoglobulinas é diminuída e há formação de memória imunológica celular. Portanto, no caso de uma nova exposição, haverá uma grande produção de imunoglobulinas levando ao aparecimento da doença em potros de éguas sensibilizadas. Os principais sinais clínicos são anemia e icterícia, devendo ser diferenciados de outras doenças como: hemólise induzida por toxinas bacterianas, doenças do sistema hepato-biliar, hemólise pro reação a drogas e coagulação intravascular disseminada, incompatibilidade em transfusões de sangue e babesiose. Como a sensibilização ocorre durante o nascimento prévio de um potro co hemácias incompatíveis, a doença acomete com maior freqüência potros de éguas multíparas. Porém, uma égua primípara 5 pode gerar um potro com isoeritrólise neonatal se tiver recebido uma transfusão sensibilizante prévia ou desenvolvido anormalidades placentárias no início da prenhez que tenham levado ao derramamento de eritrócitos fetais em sua circulação
Keywords: Equino - Reprodução; Neonatologia veterinária; Potro - Doenças; Equine - Diseases